Writing Jewish culture : paradoxes in ethnography - Kilcher, Andreas B., 1963-; Weissberg, Liliane (Indiana University Press, 2016)
Focusing on Eastern and Central Europe before WWII, this collection explores various genres of "ethnoliterature" across temporal, geographical, and ideological borders as sites of Jewish identity formation and dissemination. Challenging the assumption of cultural uniformity among Ashkenazi Jews, the contributors consider how ethnographic literature defines Jews and Jewishness, the political context of Jewish ethnography, and the question of audience, readers, and listeners. With contributions from leading scholars and an appendix of translated historical ethnographies, this volume presents vivid case studies across linguistic and disciplinary divides, revealing a rich textual history that throws the complexity and diversity of a people into sharp relief.---publisher website.